Optimisation of a mixed flow fan with NACA profiled blades using computational fluid dynamics. (2nd September 2020) - Aydin, Ahmet; Yigit, Cemil; Engin, Tahsin; Akkoc, Huseyin
In this study, the optimisation of a mixed flow fan, which is widely used in industrial applications has been made using computational fluid dynamics. In the optimisation process, the CAD file of the mixed flow fan, which can operate under the specific conditions, has been created and preliminary design has been realised. Blade angle, wall thickness and length parameters were taken, and the blades have been optimised by using Ansys/response surface optimisation (RSO) tool. Fans were produced in preliminary and optimised design, and experimental studies were carried out in a laboratory. As a result of optimisation, the maximum shaft power of the design-improved mixed flow fan was reduced by 8.62%, while an increase of 8.70% in total pressure value for the best operating point was achieved. In addition, the yield of the mixed flow fan was increased by 16.42%, while the sound pressure level has been decreased by 1.52%.